The Effectiveness of Cognitive-Behavioral Guidance Program in Reducing the Level of Addiction on Social Media in a Sample of High School Students in Karak Schools (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current research aims to develop a guidance program suitable for high school students and apply it to them in order to ensure the reduction of addiction to the use of different means of communication. The researchers used the scale of addiction to the means of communication (SAS) to measure the level of addiction as well as to identify the impact of the proposed guidance program in reducing the degree of addiction to communication. It was applied to a sample of (20) female students divided equally into two groups: an experimental group of (10) female students and a control group of (10) female students from the secondary level in a school under the department of education in the education of the almazar in Karak / Jordan. The extension program was implemented for a month with two sessions a week. The results indicated there are statistically significant differences in reducing the level of addiction in favor of the experimental group compared to the control group at the level of indication, which confirms the effectiveness and the impact of the program in causing positive change appeared by reducing the number of behaviors and disorders of the students' sample, as well as the results revealed there is an escalation of the level of awareness and attention in the sample of research, which reflected on the rest of the behavior of other students through observation and self-reports. The importance of counseling and psychotherapeutic programs and services in girls’ schools at all stages in reducing the level of addiction for users of various means of communication on the Internet and in our societies to avoid harmful consequences.